Characterization of Some Nigerian Coals for Power Generation - M. Chukwu; C. O. Folayan; G. Y. Pam; D. O. Obada (Journal of Combustion)
Five coal samples from Odagbo (Kogi State), Owukpa (Benue State), Ezimo (Enugu State), Amansiodo (Enugu State), and Inyi (Enugu State) of Nigerian coal deposits were subjected to proximate analysis, ultimate analysis, calorific value determination, and petrographic and thermogravimetric analysis to determine their suitability for power generation. Based on results of tests carried out, Amansiodo coal is a bituminous, low sulphur, and medium ash coal, while Owukpa coal is a subbituminous A, low sulphur, low ash coal rich in huminites, Odagbo coal is a subbituminous B, medium sulphur, low ash coal rich in huminites, Ezimo coal is a subbituminous C, low sulphur, high ash coal, and Inyi coal is a subbituminous C, low sulphur, high ash coal. Between Odagbo and Owukpa subbituminous coals, Owukpa has a lower ignition temperature (283.63°C) due to its higher volatile matter content (39.1%). However, Ezimo subbituminous coal, which has a lower volatile matter (31.1%), unexpectedly has the same ignition temperature as Owukpa (283.63°C) due to its higher liptinite content (7.2%) when compared with that of Owukpa (2.9%). The ease of combustion of the coal samples in decreasing order is Odagbo < Owukpa < Inyi < Ezimo < Amansiodo.